ANALYSIS OF THE COMMUNITY'S DECISION IN CHOOSING BAZNAS TO PAY ZAKAT: A CASE STUDY OF ROKAN HULU REGENCY - Meriastuti Meriastuti; Fajar Fadly (LPPM Universitas Abdurrab, 2026)
This study aims to find out the reasons for the people of Rokan Hulu in choosing Baznas to pay Zakat. This study uses a qualitative descriptive method. The data collection technique in this study uses questionnaires, observations, and documentation. The results of the study are seen from the decision variables with product indicators, promotion, place, physical evidence, people, peoses, and decisions. Based on the results of the study, it shows that the community's decision to choose BAZNAS as a place to pay zakat is because it has trust. The reason why people pay zakat is because the introduction process to the community is well done, the location of the Baznas office is strategic and easy to reach, Baznas also has an attractive interior, has used technological tools to support all transactions, Baznas employee staff are friendly and neat, providing detailed and detailed information. So that it makes people pay their zakat to BAZNAS again.